2016
DOI: 10.5897/ajar2015.10060
|View full text |Cite
|
Sign up to set email alerts
|

Abundance and distribution of Striga (Striga hermonthica (Del.) Benth.) infestation in selected sorghum (Sorghum bicolour L. Moench) growing areas of Tigray Region, Ethiopia

Abstract: (16) respectively. Whereas, the lowest density of Striga shoots per plant of sorghum was registered at Genetie (4), Mentebteb (4), Rawyan (5), May Shek (7), Kara Adishabo (7) and Mitsa Werki (7). The highest level of Striga infestation was recorded at sites which had got the highest population density of sorghum, sites with low organic matter and available soil phosphorous content and sandy textured soils. Management practices channeled towards improving these limitations have been suggested for controlling of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Several studies have highlighted the widespread infestation of S. hermonthica in different parts of Ethiopia. Atsbha Gebreslasie et al (2016) reported moderate to severe infestation throughout Tigray, While Lemma Degebasa et al (2022) found that S. hermonthica was the dominant species (up to 92%) in Eastern and Western Hararghe, Oromia. In Benishangul Gumuz, Ethiopia, S. hermonthica poses a serious challenge to sorghum production across almost all districts.…”
Section: Introductionmentioning
confidence: 98%
“…Several studies have highlighted the widespread infestation of S. hermonthica in different parts of Ethiopia. Atsbha Gebreslasie et al (2016) reported moderate to severe infestation throughout Tigray, While Lemma Degebasa et al (2022) found that S. hermonthica was the dominant species (up to 92%) in Eastern and Western Hararghe, Oromia. In Benishangul Gumuz, Ethiopia, S. hermonthica poses a serious challenge to sorghum production across almost all districts.…”
Section: Introductionmentioning
confidence: 98%